Domestic Violence and the Way Forward - Ingrid Westendorp (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2010)
Even though States have undertaken more actions to protect the victims and punish the perpetrators in domestic violence cases, not enough attention is being paid to the unequal socio-economic position of women. This writing will analyse ways and means that may lead to the abolition of discrimination against women.  Walaupun Negara telah berupaya menghukum pelaku kekerasan dalam rumahtangga dan melindungi korbannya, perhatian terhadap posisi sosio-ekonomi wanita masih belum cukup diberikan. Tulisan ini akan menganalisis upaya-upaya yang dapat dilakukan untuk mengakhiri tindakan diskriminatif terhadap hak-hak wanita.